Evaluation of the Political Marketing Model with a Focus on Individual Behavior Components - Marandi, Mohammad; Safarzadeh, Hossein; Aligholi, Mansoureh (Management Strategies and Engineering Sciences, 2025)
The present study aims to design and explain a political marketing model with a focus on individual behavior components. The data collection method in this study was conducted using both library research and field research. The data collection tool in the quantitative section was a researcher-made questionnaire, developed based on the results of the qualitative section and distributed among 310 individuals using non-probability random sampling. For qualitative data analysis, inductive qualitative content analysis was employed. For quantitative data analysis, descriptive statistics were used, and for examining the research questions, inferential statistics and the partial least squares (PLS) method were applied using SPSS and SMARTPLS software. The study's findings indicate that individual factors, including variables such as political awareness, vote market needs assessment, and value creation for voters, play a key role in stimulating and directing voter behavior. Marketing and media factors include variables such as media framing, effective marketing and advertising, branding, and the development of a new paradigm in political marketing. Additionally, environmental and technological factors encompass variables such as technological changes, international pressures, and continuous environmental monitoring. These factors, as external variables, shape the political and social environment and influence marketing strategies. However, leveraging voters’ political awareness to develop targeted electoral messages and designing political marketing strategies with an emphasis on technology and media can create greater impact.